2005
DOI: 10.1002/ps.1098
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal gene transfer of atrazine‐degrading genes (atz) from Agrobacterium tumefaciens St96‐4 pADP1::Tn5 to bacteria of maize‐cultivated soil

Abstract: The plasmid pADP1::Tn5 derived from pADP1[Atr+] carrying a Tn5 transposon conferring kanamycin and streptomycin resistances was constructed and introduced in Agrobacterium tumefaciens St96-4. This genetically modified strain was inoculated (approximately 10(8) cfu g(-1)) in potted soils planted with maize and treated or not with atrazine (1.5 mg kg(-1)). Bulk and maize rhizosphere soils were sampled 39 days after planting to look for soil indigenous bacteria that had acquired pADP1::Tn5. Four transconjugants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 59 publications
3
49
0
2
Order By: Relevance
“…According to this, studies revealed that atzABC genes were widespread, having been detected in Canada, U.S.A., France, Croatia and China, and were also highly conserved (>97% similarity) indicating their recent dispersion within soil microflora (de Souza, 1998a;Rosseaux et al, 2001;Devers et al, 2004). Devers et al (2005) demonstrated that the atrazine-degrading plasmid ADP1::Tn5 was transferred from Agrobacterium tumefaciens St96-4 to soil microflora at a frequency of 10 -4 per donor cell. In two of the gram-negative transconjugants isolated, namely Variovorax sp.…”
Section: Atrazine Degradation By Bacteriamentioning
confidence: 94%
“…According to this, studies revealed that atzABC genes were widespread, having been detected in Canada, U.S.A., France, Croatia and China, and were also highly conserved (>97% similarity) indicating their recent dispersion within soil microflora (de Souza, 1998a;Rosseaux et al, 2001;Devers et al, 2004). Devers et al (2005) demonstrated that the atrazine-degrading plasmid ADP1::Tn5 was transferred from Agrobacterium tumefaciens St96-4 to soil microflora at a frequency of 10 -4 per donor cell. In two of the gram-negative transconjugants isolated, namely Variovorax sp.…”
Section: Atrazine Degradation By Bacteriamentioning
confidence: 94%
“…The presence of atrazine degradation genes on different size plasmids, suggests widespread of atrazine degradation genes among unrelated bacteria was not exclusively due to direct plasmid transfer. Furthermore, this view was further confirmed by the finding of bacteria with different combinations of atrazine degradation genes such as including trzN-atzBC, atzABC-trzD, and atzABCDEF (Devers et al, 2005). Atrazine catabolism initiated by triazine hydrolase TrzN, in a…”
Section: Genetic Basis Of Atrazine Biodegradationmentioning
confidence: 77%
“…This phenomenon could be explained on the basis of the fact that these functional genes have possibly undergone horizontal transfer from one organism to the other irrespective of their taxonomic ranks. It is well documented that horizontal gene transfer is responsible for diversity and distribution of catabolic gene(s) involved in the degradation of naphthalene, atrazine etc [27,28].…”
Section: Resultsmentioning
confidence: 99%